2024
DOI: 10.3847/1538-4357/ad1e5f
|View full text |Cite
|
Sign up to set email alerts
|

UNCOVER Spectroscopy Confirms the Surprising Ubiquity of Active Galactic Nuclei in Red Sources at z > 5

Jenny E. Greene,
Ivo Labbe,
Andy D. Goulding
et al.

Abstract: The James Webb Space Telescope is revealing a new population of dust-reddened broad-line active galactic nuclei (AGN) at redshifts z ≳ 5. Here we present deep NIRSpec/Prism spectroscopy from the Cycle 1 Treasury program Ultradeep NIRSpec and NIRCam ObserVations before the Epoch of Reionization (UNCOVER) of 15 AGN candidates selected to be compact, with red continua in the rest-frame optical but with blue slopes in the UV. From NIRCam photometry alone, they could have been dominated by dusty star formation or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 146 publications
12
59
2
Order By: Relevance
“…The spectral properties mentioned above suggest the presence of quasars in both sources. The widths of the Lyα broad components exceed the common threshold of quasar classification, v FWHM = 500-1000 km s −1 (e.g., Schneider et al 2010;Pâris et al 2012), and are similar to values found in faint AGNs revealed by JWST spectroscopy of EoR galaxies (e.g., Greene et al 2024;Harikane et al 2023;Maiolino et al 2023). These values are found at the lower end of the FWHM distribution of low-z Seyfert 1 galaxies in SDSS (e.g., Hao et al 2005) and of high-z low-luminosity quasars found in SHELLQs.…”
Section: Nature Of the Two Sourcessupporting
confidence: 75%
See 1 more Smart Citation
“…The spectral properties mentioned above suggest the presence of quasars in both sources. The widths of the Lyα broad components exceed the common threshold of quasar classification, v FWHM = 500-1000 km s −1 (e.g., Schneider et al 2010;Pâris et al 2012), and are similar to values found in faint AGNs revealed by JWST spectroscopy of EoR galaxies (e.g., Greene et al 2024;Harikane et al 2023;Maiolino et al 2023). These values are found at the lower end of the FWHM distribution of low-z Seyfert 1 galaxies in SDSS (e.g., Hao et al 2005) and of high-z low-luminosity quasars found in SHELLQs.…”
Section: Nature Of the Two Sourcessupporting
confidence: 75%
“…In the meantime, the James Webb Space Telescope (JWST) has produced groundbreaking results in the past two years. Its extremely high IR sensitivity has revealed a weak broad component in Balmer emission lines of many high-z galaxies, signaling the presence of low-luminosity active galactic nuclei (AGNs) out to z ∼ 11 (e.g., Greene et al 2024;Maiolino et al 2023). The number density of such AGNs exceeds the extrapolation of the classical QLF by several orders of magnitude (e.g., Harikane et al 2023;Matthee et al 2024), changing the paradigm of SMBH activity happening in the EoR.…”
Section: Introductionmentioning
confidence: 99%
“…The BH masses for those JWST-detected faint AGNs are M • ∼ 10 6−8 M e , which is 1-2 orders of magnitude lower than those of previously known quasars at z > 4. Intriguingly, some of the sources have extremely red colors in the rest-frame optical bands, while the rest-frame UV color seems fairly consistent with those of known Lyman-break galaxies at similar redshifts (e.g., Harikane et al 2023;Kocevski et al 2023;Labbe et al 2023;Barro et al 2024;Greene et al 2024;Matthee et al 2024). The so-called "little red dot" sources are interpreted to be in a transition stage from a dust-obscured starburst to an unobscured luminous quasar due to the expelling of gas and dust (Fujimoto et al 2022).…”
Section: Introductionsupporting
confidence: 59%
“…Notably, Ricarte & Natarajan (2018) predict bolometric luminosity functions for accreting SMBHs at a range of redshifts for the light and heavy seed models. In Figure 4, we compare the Ricarte & Natarajan (2018) model predictions of AGN luminosity functions at z ∼ 10 based on UHZ 1 and GHZ 9 and at z = 6-8.5 using data from Greene et al (2024). The observed AGN number density at z = 6-8.5 exceeds the theoretical expectations for the light and heavy seed models.…”
Section: Discussionmentioning
confidence: 86%